La educación moral durkheimiana y la crisis de la esfera educativa en el mundo tardo-moderno - Durán Vázquez, José Francisco (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
The education is at present one of the social areas that is more an object of different debates, the majority of which try to give response to what it is considered to be almost unanimously a situation of crisis. In the article that later we sense beforehand we want to give our particular vision of this crisis, departing for it from the educational offer Durkheimiana. Since Durkheim’s work is mostly, since it is known, an attempt of constructing a new moral order that was solving the crisis of the order estamental and that the new industrial society was legitimizing at the same time, and provided that her approach has coincided essentially with the principles that the modern societies have articulated, the above mentioned work looks like to us a good starting point to analyze the sense of this crisis, directly related to that of these societies. The first part of the article will be dedicated to showing, so, Durkheim’s point of view on the moral education, in the context of his particular worries for building a moral order in agreement with the needs of the industrial society. In the last part, we will analyze the contradictions that slow modernity the educational systems suffer in it, putting in relation this fact so much with the new social realities, like with the offer Durkheimiana, which, as we were saying previously, it coincides with her most with the ideology of the modern societies.